Culorile Noului Val Românesc. Simbolism și semnificații psihologice / The Colors of the Romanian New Wave. Symbolism and psychological significance - Candel, Octav Sorin (Swedish Journal of Romanian Studies, 2018)
Recent Romanian films continue to be appreciated by critics and to receive important international awards. This, along with a series of common techniques and themes, led to the emergence of the term "the Romanian New Wave", a term assumed by some critics and directors and rejected by others. In this article, I aim to check if the use of colors is a technique that characterizes the films reunited under this umbrella term. In order to do so, I analyzed five films from different years but overall accepted as part of the New Wave. These are Marilena from P7, 4 months, 3 weeks and 2 days, Best intentions, Child’s Pose and Self-Portrait of a Dutiful Daughter. I was interested in discovering the symbols associated with each color, while also emphasizing their psychological meaning. Another goal was to check if and how the chromatic aspects were related to the social reality presented in each movie. Finally, I presented the common features of the films and the differences between them.